The music of the Netherlands Antilles : why eleven Antilleans knelt before Chopin's heart - Brokken, Jan (Caribbean studies series (Jackson, Miss.), 2015)
An exploration of an overlooked Caribbean musical tradition and the European, African and New World influences that created it.